Software Architecture Superstream. (O'Reilly Media, Inc., 2023)
Frontend developers and architects combine interface design skills and programming excellence to ensure that users can easily interact with their organizations' web pages. As the demand for online goods continues to grow, developers, architects, and designers will need to consider the efficiency, scalability, performance, and security of their websites to best support their customers. The rise of new language frameworks and micro-frontends means that it's now possible to create truly decoupled user interfaces leading to faster deploying and more scalability. Join leading experts and practitioners from the field for a deep dive into the discipline of frontend architecture. You'll gain insight into the latest tools, standards, and best practices that have elevated frontend web development to an entirely new level. What you'll learn and how you can apply it Understand how cloud native and the Web Platform APIs are pushing the boundaries of what was once known as the Jamstack and micro-frontends into a full stack composable architecture Learn what the future holds for frontend developers This recording of a live event is for you because... You're a software architect or developer working on or thinking about working on frontend architectures and want to learn best practices. You want to effectively develop your frontend architecture into a system where user data is "at the beck and call of the users themselves" for a more user-centric experience. Recommended follow-up: Listen to Blazor in Action (audiobook) Read Building Micro-Frontends (book) Read Micro Frontends in Action (book).